The Varieties of Legal History - Michael Lobban (Clio@Themis)
This article looks at the different approaches which have been taken in the study of legal history in England and America by both historians in law and history faculties. The pioneer English legal historian was F.W. Maitland, who felt that the skills of the lawyer were needed to understand the legal materials which were the source of much medieval social and economic history. Maitland, who had no wish to use history to explain current doctrine, inspired a generation of medieval historians to look at legal questions. The study of legal history in English law schools was in turn revolutionized by S. F. C Milsom, who felt that the key to legal history was not to apply the skills of the present lawyer to the law of the past, but to attempt to get into the minds of previous generations of lawyers. Following Milson, doctrinal legal history flourished in England. In the United States, a different tradition dominated law schools. Here, the pioneer was J. Willard Hurst, who turned attention away from narrow doctrinal history, to a broader contextual study of law, looking at the operation of law in society. The article discusses the kind of historiography which developed in America after Hurst, before turning to what discuss what role doctrinal legal history can continue to play, both to inform historical and legal debates.